2015
DOI: 10.3329/bjpp.v30i2.22677
|View full text |Cite
|
Sign up to set email alerts
|

Study of autopsy based suicidal hanging

Abstract: Introduction: Hanging is one of the most commonly used methods for suicide in most countries. Commission of suicide by hanging is increasing in the people of Bangladesh. Suicidal hanging is detrimental to social health. Appropriate measures to prevent it are essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…Regarding the degree of suspension, we found that majority of the victims were completely suspended (79.22%). This finding is in agreement with similar study observed by Ahmad M et al 14 and Talukder N et al 17 Ahmad M et al 14 found 97% victims were completely suspended and Talukder N et al 17 found that 90% hanging cases had complete suspension. In Post mortem report findings, our study found that majority of the ligature marks on neck was present above the thyroid cartilage 138(89.61%), over the thyroid cartilage 12(7.79%) and below the thyroid cartilage 04(2.60%).…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the degree of suspension, we found that majority of the victims were completely suspended (79.22%). This finding is in agreement with similar study observed by Ahmad M et al 14 and Talukder N et al 17 Ahmad M et al 14 found 97% victims were completely suspended and Talukder N et al 17 found that 90% hanging cases had complete suspension. In Post mortem report findings, our study found that majority of the ligature marks on neck was present above the thyroid cartilage 138(89.61%), over the thyroid cartilage 12(7.79%) and below the thyroid cartilage 04(2.60%).…”
Section: Discussionsupporting
confidence: 92%
“…20 Almost similar observations were made by a good number of authors. 12,13,18,19 In present study cyanosis of fingertips and nail beds of both hands was the commonest finding followed by pale, white, hard, and glistening subcutaneous tissue underneath the ligature mark and dribbling marks of saliva. These findings are the most important signs of asphyxia and are mentioned in every literature available.…”
Section: Discussionmentioning
confidence: 96%
“…11,15 Most of the previous studies done in Bangladesh reported similar trend with a negligible exceptions in a few studies. [17][18][19][20] Majority of victims used dopatta (orna) followed by nylon rope, sari and electric wire. Ali et al reported that soft material like orna, saree, and cloth were the preferred material for hanging in their study followed by firm materials like rope.…”
Section: Discussionmentioning
confidence: 99%
“…Still our economy is agricultural-based. Both hanging and poisoning are preferable to existing culture as well and insecticides are lethal, easily available, accessible, poor storage can be the causes for choosing (Feroz & et al, 2012, Ali & et al, 2014; Wu, Chen, & Yip, 2012; Talukder, Karim, Chowdhury, Habib, Chowdhury & Perveen, 2014). Regarding hanging Dopatta (orna) was the most common ligature material (Wu, Chen, & Yip, 2012; Talukder, Karim, Chowdhury, Habib, Chowdhury & Perveen, 2014); wherein report from another study rope was the most common ligature material in hanging (Hossain, Rahman & Akhter, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…However, the age's ranges from 10 to 78 years (Wu, Chen, & Yip, 2012;Ali & et al, 2014) but most prevalent age group is age under 40 years. The distribution of age was revealed from different study including the most common age is 20-29 years (Feroz&et al, 2012); 20-40 years (Ali & et al, 2014); 20-35 years (Wu, Chen, & Yip, 2012);21-30 years (Ali & et al, 2014);below 30 years (Talukder, Karim, Chowdhury, Habib, Chowdhury & Perveen, 2014);and18-40 years (Sarkar, Shaheduzzaman, Hossain, Ahmed, Mohammad & Basher, 2013) age group. The mean age of male was 28.86 ± 11.27 years with age range of 8-70 years and the mean age of female was 25.31 ± 7.70 years with age range of 11-78 years (Ali & et al, 2014).…”
Section: Age and Gender Distributionmentioning
confidence: 99%